Common Variants Coregulate Expression of GBA and Modifier Genes to Delay Parkinson's Disease Onset - Schierding, William; Farrow, Sophie; Fadason, Tayaza; Graham, Oscar E.E.; Pitcher, Toni L.; Qubisi, Sara; Davidson, Alan J.; Perry, Jo K.; Anderson, Tim J.; Kennedy, Martin A.; Cooper, Antony; O'Sullivan, Justin M. (Movement disorders, 2020)
Background GBA mutations are numerically the most significant genetic risk factor for Parkinson's disease (PD), yet these mutations have low penetrance, suggesting additional mechanisms. Objectives The objective of this study was to determine if the penetrance of GBA in PD can be explained by regulatory effects on GBA and modifier genes. Methods Genetic variants associated with the regulation of GBA were identified by screening 128 common single nucleotide polymorphisms (SNPs) in the GBA locus for spatial cis‐expression quantitative trail locus (supported by chromatin interactions). Results We identified common noncoding SNPs within GBA that (1) regulate GBA expression in peripheral tissues, some of which display α‐synuclein pathology and (2) coregulate potential modifier genes in the central nervous system and/or peripheral tissues. Haplotypes based on 3 of these SNPs delay disease onset by 5 years. In addition, SNPs on 6 separate chromosomes coregulate GBA expression specifically in either the substantia nigra or cortex, and their combined effect potentially modulates motor and cognitive symptoms, respectively. Conclusions This work provides a new perspective on the haplotype‐specific effects of GBA and the genetic etiology of PD, expanding the role of GBA from the gene encoding the β‐glucocerebrosidase (GCase) to that of a central regulator and modifier of PD onset, with GBA expression itself subject to distant regulation. Some idiopathic patients might possess insufficient GBA‐encoded GCase activity in the substantia nigra as the result of distant regulatory variants and therefore might benefit from GBA‐targeting therapeutics. The SNPs’ regulatory impacts provide a plausible explanation for the variable phenotypes also observed in GBA‐centric Gaucher's disease and dementia with Lewy bodies. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, LLC on behalf of International Parkinson and Movement Disorder Society.